1987
DOI: 10.1111/j.1559-1816.1987.tb00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with AIDS: Psychological and Health Implications1

Abstract: The current study explored the relationship of coping to both psychological and health parameters in 50 gay men recently (within three months) diagnosed with AIDS. Three methods of coping (active behavioral, active cognitive, and avoidance) and eight different coping strategies (positive involvement, expressive/ information seeking, reliance on others, positive understanding/create meaning, passive/ruminative, distraction, passive resignation, and solitary/passive behaviors) were assessed. Findings indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
134
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(144 citation statements)
references
References 14 publications
8
134
1
Order By: Relevance
“…In this study, emotionally-sustaining social support was rated by the patients to be more desirable than practical support (particularly when coming from lovers, friends or families). Moreover, the possibility was considered that the sickest patients may receive less social support because they are not able to take it up (a finding which is consistent with the observation by Namir et al (1987) that patients relying on avoidance as a coping style receive less support since they are seen as less motivated and attractive by support givers). Finally, adjustment disorders have been found to be more frequent in subjects with ARC than in those with AIDS (Temoshok et al 1986;Tross et al 1986), which finding has been ascribed to the greater level of uncertainty about the future in subjects with mid-stage manifestations of the disease.…”
Section: Adjustment Disorders Psychological Backgroundsupporting
confidence: 72%
See 1 more Smart Citation
“…In this study, emotionally-sustaining social support was rated by the patients to be more desirable than practical support (particularly when coming from lovers, friends or families). Moreover, the possibility was considered that the sickest patients may receive less social support because they are not able to take it up (a finding which is consistent with the observation by Namir et al (1987) that patients relying on avoidance as a coping style receive less support since they are seen as less motivated and attractive by support givers). Finally, adjustment disorders have been found to be more frequent in subjects with ARC than in those with AIDS (Temoshok et al 1986;Tross et al 1986), which finding has been ascribed to the greater level of uncertainty about the future in subjects with mid-stage manifestations of the disease.…”
Section: Adjustment Disorders Psychological Backgroundsupporting
confidence: 72%
“…Subject's coping strategies are certainly involved: Namir et al (1987) have shown that the style of coping adopted by subjects with a recent diagnosis of AIDS was predictive of their psychological wellbeing, with the highest levels of depression found in those who relied upon avoidance of the reality of the diagnosis, and the highest frequency of obsessive thoughts in those adopting an active-cognitive coping style (involving 'the building of mental defences and the development of a sense of meaning about their illness'). Reservations about homosexuality or lifestyle also seem to be important: in subjects who have internalized social non-acceptance of homosexuality or drug abuse, the diagnosis of HIV-1 infection may be taken as an evidence of past 'wrong doing', thus generating feelings of guilt and self-depreciation (Hays & Lyles, 1986;Miller, 1988).…”
Section: Adjustment Disorders Psychological Backgroundmentioning
confidence: 99%
“…Researchers have demonstrated that persons who perceive fewer threats in their environment and who cope more adaptively experience lower levels of emotional distress (Fawzy et al, 1990;Namir, Wolcott, Fawzy, & Alumbaugh, 1987) and engage in less risky behaviors (Nyamathi, Wayment, et al, 1993). The impact of threat appraisal on barriers to condom use is likewise of interest in this study.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…These responses can be described as active or adaptive coping behaviors that manage problems or avoidant behaviors that ease the emotional distress experienced. Research has outlined the relationship between personal resources and adaptive coping (Gutierres & Reich, 1988;Tucker, 1982) and of adaptive coping with lower levels of risky behavior and emotional distress (Fawzy et al, 1990;Namir et al, 1987).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Coping Style-Coping style was measured with a modified 39-item version of the Dealing with Illness Inventory (Namir, Wolcott, Fawzy, & Alumbaugh, 1987;Murphy, RotheramBorus, & Marelich, 2003). The measure asks how often particular coping strategies are used to help deal with knowing that one is HIV positive during the previous three months.…”
Section: Action Contextmentioning
confidence: 99%